The Influence of Financialization on Industrial Development: An Empirical Analysis in China - Chen, Xiaoyu (Archives of Business Research, 2015)
The effect of China’s financialization on industrial development is examined in this paper. To make the research more specifically, industrial development has been divided into three parts, namely industrial rationalization, upgrading and stabilization. Using data from 1978 to 2012, the influence of financialization on industrial rationalization, upgrading and stabilization is examined, with the empirical methods of Cointegration test, Granger Causality test and Impulse Response analysis. Although evidences from developed countries show that the development of finance can promote industrial development in many ways, the results in this paper indicate that China’s financialization suppresses industrial stabilization, which can be explained by the low level of financialization accompanied with a lack of supervision. However, we still find the positive effects from financialization to industrial structure upgrading and rationalization. These empirical results are consistent with theoretical analysis developed by post Keynesian economics. The results concluded from this paper also have implications to other developing countries.